2022
DOI: 10.1039/d2ce00138a
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions during the water sorption process in two layered metal hydrogen-bonded organic frameworks and the effect of the H-bond strength between the layers

Abstract: The supramolecular network material [Co(amp)3][Cr(ox)3] (amp = 2-aminomethylpyridine, ox = oxalate) (I’) shows in its powder X-ray diffraction (PXRD) carpet plot during the water adsorption process two sets of diffraction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Rahmani et al found that nonporous TPBD allows for highly selective capture of p -xylene, undergoing a structure transformation from TPBD to TPBD-PX . Molecular crystals with hydrophilic functional groups, such as amino and 2,4-diamino triazine (DAT) groups might be promising adsorbent materials for selective recognition and separation of water. …”
mentioning
confidence: 99%
“…Rahmani et al found that nonporous TPBD allows for highly selective capture of p -xylene, undergoing a structure transformation from TPBD to TPBD-PX . Molecular crystals with hydrophilic functional groups, such as amino and 2,4-diamino triazine (DAT) groups might be promising adsorbent materials for selective recognition and separation of water. …”
mentioning
confidence: 99%